The wizard's tale - Busiek, Kurt (IDW Pub., 2010)
Bafflerog Rumplewhisker is an evil wizard whose job is to find the long-lost Book of Worse, which holds magical spells that can crush the forces of goodness and light forever. There's only one problem. This kindhearted wizard's heart's just not into it. So what does he do when he has to go on a quest to end all hope and light and freedom for everyone in the world?